The Best (and Worst) of GHG Emission Trading Systems: Comparing the EU ETS with Its Followers - Borghesi, Simone; Montini, Massimiliano (Frontiers in Energy Research, 2016)
The European Emission Trading System (EU ETS) is generally considered as the prototype system for the other Emission Trading Systems (ETSs) for the reduction of greenhouse gases (GHGs) that are rapidly spreading around the world. To get a deeper understanding on the actual capacity of the EU ETS to stand as a model for the other ETSs, the present paper discusses the differences and similarities of the EU ETS with respect to the other main ETSs and the emerging trends that these systems seem to share, comparing the different cap-and-trade regimes in order to identify the best practices and the desirable features that future ETSs should have. As emerges from the comparative analysis performed in this article, although the followers share some common flaws with the EU ETS, they have also shown the capacity to innovate and possibly devise alternative ways to manage their own ETS regimes, which may in the long term jeopardize the EU leadership in the ETSs context.